Polarization of perception and motivation in ecotourism development based on sustainable peat ecosystem utilization. Issue 1 (November 2021) - Karlina, E; Takandjadji, M; Heryati, Y; Sukmana, A; Andriani, S
Abstract: Tourism development in Indonesia is currently one of the alternatives in the national program as an effort to economic growth. The study's objectives are (1) analyzing the perception and motivation values of the stakeholder community; (2) developing a strategy to optimize the development of sustainable peat ecosystem ecotourism. The research result shows that the polarization of perception and motivation of the community and stakeholders expressed a positive attitude towards the ecotourism development in the values of 6-7. The value shows a positive attitude between the community and stakeholders. The motivational value of both actors illustrates an optimistic attitude in the ecotourism development with a value between 6-7. The results of the matrix calculation of internal and external factors produce X coordinates of 0.50 and Y – 0.50 on the strategy quadrant diagram. The strategy is Weakness-Opportunity which is a strategy that minimizes weaknesses and takes advantage of existing opportunities. Strategic formulation, namely: (1) building and strengthening institutional systems; (2) improving the welfare of the community by opening business opportunities; (3) developing infrastructure and tourism support facilities; and (4) targeting marketing programs. The research benefit is that it can be used as one of the basis in drawing up a plan to optimize the utilization of peat ecosystems sustainably. It also can improve local communities' attitudes of concern, awareness, and welfare.